THE CREATIVITY AND INDEPENDENCE OF STUDENTS THROUGH EDGEPLAY MATE MEDIA IN ELEMENTARY SCHOOL - Putri Zudhah Ferryka; Ria Devitasari; Rizki Alifianto; Sayyidah Fatimah Nurdin; Septi Irawati; Shofiya Izzatu Syahida (El Midad, 2025)
This study aims to improve the creativity and independence of 5th-grade students of SDN 2 Karangan in science by applying game-based learning media, Eduplay Mate. The method used is the Classroom Action Research (CAR) model, by Kemmis and McTaggart, which consists of four stages: planning, implementation, observation, and reflection. The study subjects were 29 5th-grade students of SDN 2 Karangan. Data collection techniques were collected through observation, interviews, documentation, and questionnaires. Data analysis used qualitative descriptive techniques. The study results showed that using Eduplay Mate can improve students' creativity and independence. As many as 75% of students showed increased creativity and independence based on the results of observations and questionnaires. In addition, 80% of students responded positively to Eduplay Mate-based learning. In conclusion, Eduplay Mate is efficacious in improving students' creativity and independence in science.